Pseudoexfoliation syndrome-associated genetic variants affect transcription factor binding and alternative splicing of LOXL1 - Francesca Pasutto (Nature Portfolio, 2017)
LOXL1 is a genetic risk factor for pseudoexfoliation syndrome of the eye but a causal variant has not been identified. Here, Pasutto et al., find intronic LOXL1 risk variants influence transcription factor binding and alternative splicing of LOXL1 in affected tissues reducing levels of LOXL1mRNA.